2018
DOI: 10.1139/cjss-2017-0115
|View full text |Cite
|
Sign up to set email alerts
|

Short-term changes in spruce foliar nutrients and soil properties in response to wood ash application in the sub-boreal climate zone of British Columbia

Abstract: Utilization of wood ash as a forest soil amendment in British Columbia could have numerous benefits, including potentially increasing tree growth. Two wood-derived bottom ashes (low-carbon gasifier ash and high-carbon boiler ash) were applied at 5000 kg ha −1 (dry weight equivalent) with urea (100 kg N ha −1 ), in a twoway factorial randomized block design across two (18-and 24-yr-old) hybrid spruce (Picea glauca × engelmannii Parry × Engelm.) plantations in interior British Columbia. Changes in spruce foliar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 57 publications
(155 reference statements)
1
6
0
Order By: Relevance
“…1 site; Table 4), forest floor pH increased in the first year following application of 2 Mg•ha −1 or 8 Mg•ha −1 of wood ash, and treatment effects remained constant at years 2 and 5 (Brais et al 2015). In a white spruce (Picea glauca (Moench) Voss) plantation in northcentral British Columbia, forest floor pH had increased five months after the application of 5 Mg•ha −1 low-carbon gasifier ash or highcarbon boiler ash; treatment effects were strongest following the application of gasifer ash, particularly when applied in combination with 100 kg•ha −1 urea (Domes et al 2018). In all of the above studies, wood ash application had no significant effect on the pH of the surface (0-10 cm) mineral soil.…”
Section: Lack Of Knowledge Of the Effects Of Wood Ash Applications Spmentioning
confidence: 99%
“…1 site; Table 4), forest floor pH increased in the first year following application of 2 Mg•ha −1 or 8 Mg•ha −1 of wood ash, and treatment effects remained constant at years 2 and 5 (Brais et al 2015). In a white spruce (Picea glauca (Moench) Voss) plantation in northcentral British Columbia, forest floor pH had increased five months after the application of 5 Mg•ha −1 low-carbon gasifier ash or highcarbon boiler ash; treatment effects were strongest following the application of gasifer ash, particularly when applied in combination with 100 kg•ha −1 urea (Domes et al 2018). In all of the above studies, wood ash application had no significant effect on the pH of the surface (0-10 cm) mineral soil.…”
Section: Lack Of Knowledge Of the Effects Of Wood Ash Applications Spmentioning
confidence: 99%
“…Similar to Domes et al (2018), increased soil pH was observed where a lowcarbon ash (similar to the UNBC ash type in this trial), was applied to young, 18 and 25-year old spruce stands. Our results suggested the N addition stabilized the pH somewhat.…”
Section: Discussionsupporting
confidence: 77%
“…These two kinds of ash placements were integrated into the study to determine whether the location of the ash would impact the seedlings during a vital establishment phase, particularly where a slump in nutrients can occur post-harvest (Olsson et al, 1996;Thiffault et al, 2010) Depending on the mineral content and texture of the ash, UNBC ash being finetextured compared to the chunkier CPLP ash, a type of ash stabilization prior to land application might be recommended (Jacobson, 2003). The ashes used in this study were very similar to the gasifier (UNBC) and boiler (CPLP) ashes reported by Domes et al (2018). The gasifier ash is a high mineral, low carbon ash with a greater calcium carbonate equivalence (i.e.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…There are reports of changes to soil functional and community composition due to the addition of ash throughout the literature. However these lack consistency in the amount of amendment required to elicit a response and the direction of response 19 , 22 , 48 50 . Comparing the results of these studies is further complicated by methodological differences between them.…”
Section: Discussionmentioning
confidence: 99%